2019
DOI: 10.1371/journal.pone.0215425
|View full text |Cite
|
Sign up to set email alerts
|

Emotional and social repercussions of stroke on patient-family caregiver dyads: Analysis of diverging attitudes and profiles of the differing dyads

Abstract: For patients, the social and emotional repercussions of stroke include shame, personality changes, and upheavals experienced by the couple (i.e. patient and main family caregiver). These impacts on the couple ‘patient/family caregiver’ are scarcely documented. Focusing on the perceptions of the patients and the family caregivers living at home, two years after a stroke occurrence, the aims of the study were to analyse the concordance of attitudes towards the emotional and social repercussions of stroke and to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 48 publications
2
14
0
1
Order By: Relevance
“…That is, spousal dyads tended to experience less or at least different forms of physical contact and intimacy after stroke (i.e., sexually) whereas adult child-parent dyads tended to experience more (i.e., assistance with bathing, toileting, and other personal care). Some studies in stroke include only spousal dyads (Anderson et al, 2017;Gillespie & Campbell, 2011;McCarthy et al, 2018;McCarthy & Bauer, 2015;McCarthy & Lyons, 2014), others include only adult child-parent dyads (Bastawrous et al, 2015;Hallé et al, 2011;Le Dorze et al, 2009), and others include both dyad types (Bergström et al, 2011;Bucki et al, 2019;Cramm et al, 2012;Twiddy et al, 2012). Similar to what we tell the dyads with whom we work, all cases of stroke and the relationships that follow are different.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
See 1 more Smart Citation
“…That is, spousal dyads tended to experience less or at least different forms of physical contact and intimacy after stroke (i.e., sexually) whereas adult child-parent dyads tended to experience more (i.e., assistance with bathing, toileting, and other personal care). Some studies in stroke include only spousal dyads (Anderson et al, 2017;Gillespie & Campbell, 2011;McCarthy et al, 2018;McCarthy & Bauer, 2015;McCarthy & Lyons, 2014), others include only adult child-parent dyads (Bastawrous et al, 2015;Hallé et al, 2011;Le Dorze et al, 2009), and others include both dyad types (Bergström et al, 2011;Bucki et al, 2019;Cramm et al, 2012;Twiddy et al, 2012). Similar to what we tell the dyads with whom we work, all cases of stroke and the relationships that follow are different.…”
Section: Study Strengths and Limitationsmentioning
confidence: 99%
“…However, no differences were found between spousal versus adult child-parent caregivers in perceptions of care recipient impairments, perceived quality of the relationship with the care recipient, or overall caregiving burden (Pinquart & Sorensen, 2011). Numerous studies about the psychosocial aspects of stroke have included both spousal and non-spousal caregivers (e.g., Bergström, Eriksson, von Koch, & Tham, 2011;Bucki, Spitz, & Baumann, 2019;Cramm, Strating, & Nieboer, 2012;Twiddy, House, & Jones, 2012). However, few have focused explicitly on relationship challenges.…”
Section: Introductionmentioning
confidence: 99%
“…It tends to abruptly affect individuals and caregivers in their daily life (Tsai et al, 2015). The impact of stroke on the patient and their caregiver can be physical, psychological, and social (Bucki et al, 2019). This impact can be mitigated by adhering to a set of clinical guidelines that might improve the quality-of-life of the patient and reduce the risk of a secondary occurrence.…”
Section: Introductionmentioning
confidence: 99%
“…It appears there are no other studies exploring the specific impact on significant others of their family member receiving a befriending intervention. It is notable that one recent qualitative study [34] observed discordance between stroke survivors and their caregivers when describing the social and emotional repercussions. This suggests the relative importance of an intervention to address these issues may be different to the two groups.…”
Section: Significant Other Perspectivesmentioning
confidence: 99%